Criticism of The Methods Of Interpretation Yusuf Al-Qardawi Against The Hadith Rukyat Hilal - Abdul Mufid (IAIN Tulungagung, 2020)
Abstract The main source for Muslims in understanding Islamic teachings is the Koran and Hadith. For Muslims, the Hadith second ranks after the Koran. Throughout Islamic history, hadith is a source of controversy in Islamic law. Among the problems that are still warm and almost always occur today is an understanding of the observations of the crescent related to the determination of the beginning of the Islamic month. Questioning about the differences in determining the beginning of the Hijri month is the result of different perspectives to understand the hadith about crescent observations. Therefore, the method of understanding the hadith about